PENGUKURAN KESIAPAN IMPLEMENTASI TEKNOLOGI HYPER-CONVERGED INFRASTRUCTURE DI RUMAH SAKIT BANDUNG RAYA BERDASARKAN MODEL TRI 2.0 DAN TAM - Tauchida Winanda Fadjar Setiawan; Khaerul Manaf; Beki Subaeki; Raden Muhammad Adrian Septiandry; Yanyan Gunawan (PT. Hasba Edukasi Mandiri, 2025)
Efficient information technology management has become a primary necessity for hospitals. One emerging solution is Hyper-Converged Infrastructure (HCI), which integrates computing, storage, and networking into a single platform. This study aims to assess the readiness of hospitals in the Bandung Raya region to adopt HCI, using the Technology Readiness Index (TRI) 2.0 and the Technology Acceptance Model (TAM) as the analytical framework. TRI 2.0 encompasses four psychological dimensions: optimism, innovativeness, discomfort, and insecurity. TAM is employed to evaluate perceived ease of use and perceived usefulness of the technology. The research method is quantitative, utilizing a questionnaire survey distributed to IT personnel and hospital management. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that optimism and innovativeness positively influence technology perception, while discomfort and insecurity act as psychological barriers. Positive perceptions of ease of use and usefulness further enhance readiness for HCI implementation.